Design of electric field controlled molecular gates mounted on metal–organic frameworks. Issue 18 (25th April 2017) - Tam, Benjamin; Yazaydin, Ozgur
Abstract : Molecular gates mounted on MOFs act like nanovalves and control diffusion of molecules. Abstract : In this study we propose and computationally demonstrate the concept of electric field controlled molecular gates mounted on the open-metal coordination sites in metal–organic framework (MOF) materials. The MOF-molecular gate complex functions by opening and closing under the effect of an electric field. Our design involves Mg-MOF-74, a MOF with hexagonal channels with open-metal coordination sites at each corner, and a multifunctional gate molecule with permanent dipole which anchors itself on the host MOF material and responds to changes in the direction of an electric field by rotating around its backbone which acts as an axle. By carrying out density functional theory (DFT) calculations and molecular dynamics (MD) simulations we show that the MOF-molecular gate complex can be switched between two stable configurations, open and closed, by turning on and off an external electric field. We further show that the molecular gate can be controlled to block or allow the diffusion of methane molecules through the channels of the MOF like a nanoscale butterfly valve. Electric field controlled molecular gates mounted on MOFs can pave the way for new molecular machines and nanodevices which can store, deliver or select molecules on demand and with atomic precision.